THE SOCIOLINGUISTIC INFLUENCE ON THE LEARNERS AS THE READERS (A Case Study in the Fourth Semester of English Study Program At Islamic University of Indragiri Tembilahan ) - Maizarah; Felci Tria Sauhana; Rosmina; Sipa Sapira (Program Studi Pendidikan Bahasa Inggris, 2021)
As learners of the English language, they were good readers is one of the main aims. To realize this one is not an easy act. There are many influences; one of them is sociolinguistic. This research purposed to describe the influence of sociolinguistic on the learners as the reader. This is a Descriptive Research. The research participants were the Fourth Semester of English Study Program students at the Islamic University of Indragiri Tembilahan. The data was collected from spreading the questionnaire. After analyzing the data, the researcher found a very significant influence than the other very high influence was motivation, which motivation is imperative for the learner as the reader. The mean score of all indicators was 77.93; it was indicated that the influence of sociolinguistics on the learner as the reader was great.